People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2003 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that the economy of Hong Kong Special Administrative Region (SAR) has begun to show some signs of recovery after a prolonged cyclical downturn. The highly open economy experienced a sharp output decline and large capital outflows during the Asian crisis. Domestic goods and factor prices have continued to undergo significant downward adjustment. Property prices have continued to drift downward since the collapse of the property price bubble, and are now about 60 percent below their peak attained in 1997.